2017
DOI: 10.1155/2017/2191532
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Methicillin ResistantStaphylococcus aureusand Determination of Minimum Inhibitory Concentration of Vancomycin forStaphylococcus aureusIsolated from Pus/Wound Swab Samples of the Patients Attending a Tertiary Care Hospital in Kathmandu, Nepal

Abstract: The present study was conducted to evaluate the performance of cefoxitin disc diffusion method and oxacillin broth microdilution method for detection of methicillin resistant S. aureus (MRSA), taking presence of mecA gene as reference. In addition, inducible clindamycin resistance and beta-lactamase production were studied and minimum inhibitory concentration (MIC) of vancomycin for S. aureus isolates was determined. A total of 711 nonrepeated pus/wound swab samples from different anatomic locations were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
36
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 34 publications
13
36
5
1
Order By: Relevance
“…In our study, the rate of inducible clindamycin resistance was found to be 22.4%, which was very high in comparison to the rates reported in previous studies by Ansari et al (12.4%) [13] and Adhikari et al (10%) [15] in Nepal. Such difference could be due to the difference in resistance patterns of S. aureus in different patient groups, hospitals, time periods and geographical locations [12].…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…In our study, the rate of inducible clindamycin resistance was found to be 22.4%, which was very high in comparison to the rates reported in previous studies by Ansari et al (12.4%) [13] and Adhikari et al (10%) [15] in Nepal. Such difference could be due to the difference in resistance patterns of S. aureus in different patient groups, hospitals, time periods and geographical locations [12].…”
Section: Discussioncontrasting
confidence: 53%
“…In this study, due to lack of resources we could not use molecular methods to confirm our results but there are molecular methods like coagulase (coa) gene detection by polymerase chain reaction for identification of S. aureus [19] and detection of mecA gene for identification of methicillin resistant S. aureus [15]. …”
Section: Discussionmentioning
confidence: 99%
“…However, higher rates were reported by Kshetry et al (37.6%) [6], Sanjana et al (39.6%) [20], Dibah et al (46.3%) [21], and Tiwari et al (69.1%) [22]. In a recent study from Nepal, Adhikari et al also reported higher rate of MRSA in comparison to our study [23]. The difference in the rates of isolation of MRSA in different studies might be due to the difference in the level of irrational antibiotic use, level of hygienic condition maintained in different hospitals, and effective implementation of hand hygiene program.…”
Section: Discussioncontrasting
confidence: 70%
“…Multidrug-resistant strains limit the therapeutic options, creating an economic and social burden to the healthcare system. Horizontal gene transfer in the hospital setting is responsible for disseminating antibiotic resistant determinants [26]. Therefore, the determination of accurate antibiotic susceptibility pattern is very important in the clinical care of bacterial infections, especially in organisms that possess acquired resistance mechanisms.…”
Section: Discussionmentioning
confidence: 99%